Nursing the health of the planet - Ho, Sweet Lee *; Noor Hasliza, Che Seman *; Wong, Lee Sia * (Star Media Group Berhad, 2024)
AS global health challenges increasingly intersect with environmental issues, the concept of planetary health, which emphasises the health of humans and the natural systems they depend on, has become crucial.